AI-Driven Technological Disruption, Digital Literacy, and Alumni Employability: A Quantitative Study of University Graduate - Muhammad Raja Muda Ramadhana; Khairul Amri; MHD Yavishan Novinda (PT. Maju Malaqbi Makkarana, 2026)
Introduction: The rapid development of artificial intelligence (AI) and digital transformation has created both challenges and opportunities for graduate employability, making digital literacy increasingly important in the labor market. This study aims to analyze the effect of AI technological disruption and digital literacy on the employability of FEBI UIN Ar-Raniry alumni. Methods: This research employs a descriptive quantitative approach involving 138 alumni selected through snowball sampling. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing (t-test, F-test, and coefficient of determination) using RStudio. Result: The findings demonstrate that AI technological disruption and digital literacy have a significant positive effect on employability, both individually and simultaneously.